2021
DOI: 10.1002/admi.202101296
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmonic‐Enhanced Spintronic Terahertz Emission

Abstract: operating at or below room temperature, Q is the order of meV, and this order corresponds to terahertz (THz) frequencies, which imply that future quantum devices working in THz frequency range will achieve low power consumption and high-speed performance. Electron spin, which is expected to break through the bottleneck of traditional microelectronic devices, has many excellent properties, [7,8] such as unique quantum properties, extremely low transmission energy consumption, high computing speed, high density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…The experimental results show that the intensity of the generated THz spectrum in the low-frequency band (0.1-0.5 THz) is enhanced by 2-3 orders of magnitude when the current is applied. Additionally, surface plasmonic resonance was also introduced to improve the performance for the STE by Liu et al [75]. They reported that gold nanorod (GNR) plasmonic resonance could effectively increase the terahertz emission of W/CoFeB/Pt heterostructures by 140%.…”
Section: Optimizing Structuresmentioning
confidence: 99%
“…The experimental results show that the intensity of the generated THz spectrum in the low-frequency band (0.1-0.5 THz) is enhanced by 2-3 orders of magnitude when the current is applied. Additionally, surface plasmonic resonance was also introduced to improve the performance for the STE by Liu et al [75]. They reported that gold nanorod (GNR) plasmonic resonance could effectively increase the terahertz emission of W/CoFeB/Pt heterostructures by 140%.…”
Section: Optimizing Structuresmentioning
confidence: 99%
“…Then terahertz (THz) waves with polarization perpendicular to the magnetization direction of the FM layer will be radiated 3 . Spintronic terahertz emission with high efficiency belongs to the field of light-matter interaction in physics, and many efforts have been paid to improve the efficient THz emission of STEs [4][5][6] . However, most of these efforts aimed to the THz generation process, and little research was targeted at the control and modulation the THz waves generated by the STE to improve the THz emission process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the quasi-two-dimensional geometry of the emitter allows for a direct emitter patterning ,,, or a coupling of the emitter surface to metallic microstructures , and metasurfaces, , aiming for a spectral and angular tuning of the emitted radiation, an improved excitation or outcoupling efficiency, or enhanced sensitivity in local THz spectroscopy . Up to now, spectral tunability by employing two-dimensional resonators and antennas combined with large-area illumination of the spintronic emitter yielded only moderate effects.…”
Section: Introductionmentioning
confidence: 99%